Controlling corruption In India: Various approaches and their efficacy - Verma, J.S (2011)
The topic controlling corruption in India is contextual with daily news exposing huge scams of astronomical figures, the public anger against corruption is as never before. The fierce demand for an effective Lok Pall envisaging it to be panacea for all ills has generated a heated debate on its content. A few civil society group claiming to represent the enttire nation seem to insist that the legislation be accordind to their draft. More than one such draft is in cirulation. Successive goverments' failure to act in this behalf gives legitimacy to the demand in the name of civil society, which weakens governmental authority and national institutions. It risk the constitutional fabric. There is need to channelise the public anger in the right direction to provide a solution within the constitutional framework. Approches to solve the governance issue must be tailored, accordingly. - Reproduced.
Keywords: Corruption - India; Corruption